KEEFEKTIFAN BEBERAPA DEKOMPOSER UNTUK PENGOMPLOSAN LIMBAH SLUDGE PABRIK KERTAS SEBAGAI BAHAN BAKU PUPUK ORGANIK - Widiastuti, Happy; ., Isroi; ., Siswanto (JURNAL SELULOSA, 2009)
Sludge, a solid waste by-product of paper industry, is very useful as raw materials for organic fertilizer, since this material contains carbon, and others mineral such as nitrogen, phosphorus, and pottasium. This researh evaluated 128 treatments which is combination of32 decomposers and four types of media. Thirty two decomposer are combination of 5 selected isolates i.e. omphalina sp., agrayli sp., pholyota sp., T. Pseudokoningii, and unidentified fungsi isolated from basal stem of coconut, while four types of media were sludge, sludge +cocopit, sludge+manure, sludge+cocopit+manure. composting of sludge was conducted in bag log containing 0.5 kg dry weight of sludge. Optimim condition of composting of sludge was obtained by supplementing with manure in combination with the composer (Polyota sp. And mixture of omphalina sp.+agraylie sp.+ unidentfiied fungsi isolated from basal stem of coconut). This condition can enchaane the rate of composting process, showed by reducing dry weight of compost and C concentration, and the highest percentage of carbon reducing. Application of this organic fertilizer increase the growth, N and PKey words: sludge, organic, fertilizer, nutrient tissue contentINTISARI Sludge instalasi pengolahan air limbah (IPAL) sebagai limbah pabrik padat kertas memiliki kandungan karbon organik yang tinggi juga mengandung beberapa mineral, seperti nitrogen, pospor dan kalium. Dengan karakteristik ini maka limbah padat mempunyai potensi sebagai bahan baku pupuk organik. Dalam penelitian ini diuji 128 perlakun yng merupaka kombinasi 32 jenis dekomposer terseleksi dan 4 jenis medium. 32 dekomposer yang diuji merupakan kombinasi dari 5 isolat terseleksi yaitu Omphalina sp., agrayly sp., pholyota sp., T. Pseudokoningii, dan isolat dari pangkal batang kelapa sedangkan empat jenis medium yang diuji merupakan limbak kandang, pengomposan dilakukan di bag log yang diisi0,5 kg medium. Kondisi optimum pengomposan limbah padat yang diperoleh ialah penambahan pupuk kandang yang dikombinasi dengan dekomposer yang diamati dari besarnya penurunan bobot kering kompos, persentase kadat C serta persentase penurunan kandungan CKata kunci: sludge, pupuk organik, kandungan hara jaringan